Structural model of factors affecting pmo performance in uae mega construction projects - Saleh Almansoori, Maitha Taher (2022)
Project Management Office (PMO) implementation has gained traction in a variety of fields around the world. It is gaining popularity in the construction industry as well, particularly in large and mega projects. However, in construction it is facing several challenges, including the incorporation of inexperienced managers, a lack of a clear PMO perspective, management unawareness of the scope for implementation, and a failure to follow processes that can benefit the organisation. The United Arab Emirates (UAE) construction industry is also quickly adopting PMO implementation. As a result, the purpose of this research was to investigate the factors influencing the performance of project management offices (PMOs) in the UAE construction industry. Using the SmartPLS software and the structural equation modelling technique, a structural relationship model of factors influencing PMO implementation performance in UAE mega construction projects was developed. A designed questionnaire was used to collect data in a quantitative manner. The questionnaire was validated in a pilot study by 18 UAE construction industry experts. A total of 200 questionnaires were distributed to practitioners of mega construction projects, and 171 valid responses were received with an 85.5 percent response rate. The top five factors identified by mean index and standard deviation analysis were inaccurate information reporting, a poor communication strategy, increased administrative workload, environmental challenges, and the selection of a PMO manager. The developed PLS-SEM structural model demonstrated adequate convergent and discriminant validity. The overall model was found to be satisfactory, with a goodness-of-fit (GoF) value of 0.356. The model results were then validated by ten construction experts, who determined that the overall rank generated by the PLS model can be accepted based on their knowledge and experience in PMO. As a result, the validated model is the main contribution of this study, which is the body of knowledge for the benefit of the academic community, and the model's outcomes benefited construction practitioners involved in PMO implementation, particularly in the UAE.